Human and Automatic Speaker Recognition over Telecommunication Channels - Fernández Gallardo, Laura; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This work addresses the evaluation of the human and the automatic speaker recognition performances under different channel distortions caused by bandwidth limitation, codecs, and electro-acoustic user interfaces, among other impairments. Its main contribution is the demonstration of the benefits of communication channels of extended bandwidth, together with an insight into how speaker-specific characteristics of speech are preserved through different transmissions. It provides sufficient motivation for considering speaker recognition as a criterion for the migration from narrowband to enhanced bandwidths, such as wideband and super-wideband.
Introduction -- Literature Review -- Human Speaker Identification Performance under Channel Degradations -- Importance of Intelligible Phonemes for Human Speaker Recognition in Different Bandwidths -- Automatic Speaker Verification Performance Under Channel Distortions -- Detecting Speaker-Discriminative Spectral Content in Wideband for Automatic Speaker Recognition -- Relations Among Speech Quality, Human Speaker Identification, and Automatic Speaker Verification. Conclusions and Future Work.
Keywords: Signal processing; Signal, Speech and Image Processing